Sublithostatic pore fluid pressure in the brittle–ductile transition zone of Mesozoic Yingxiu-Beichuan fault and its implication for the 2008 Mw 7.9 Wenchuan earthquake. (1st March 2016) - Han, Liang; Zhou, Yongsheng; He, Changrong; Li, Haibing
Highlights: The flow stress below the brittle-ductile transition zone of Mesozoic YBF is 15–80 MPa. Sublithostatic pore fluid pressure exists in the brittle-ductile transition zone of Mesozoic YBF. Rheological profiles combined with pore fluid pressure were constructed. Elevated pore fluid pressure would weaken the fault and allow frictional slip in a deeper depth. Abstract: In order to understand the mechanism for occurrence of large earthquakes in the Longmen Shan region, we indirectly estimated the flow stress and pore fluid pressure in the brittle–ductile transition zone by studying exhumed granitic rocks which experienced Mesozoic ductile deformation, and constructed rheological profiles for the brittle regime and transition zone. The samples were collected from a small pluton that includes granites and deformed granitic rocks overthrust at an outcrop along the southern segment of the Yingxiu-Beichuan fault. The outcrop profile consists of granitic gneiss, protomylonite and mylonite. We observed that heterogeneous ductile deformation occurred in the brittle–ductile transition zone, and that the flow stress ranges from 15 to 80 MPa. Moreover, the fault in that zone experienced a temporary brittle deformation, which might indicate a high strain rate during the co-seismic process and early post-seismic creep. Secondary fluid inclusions were found and measured to define the possible range of the capture temperature and fluid pressure. Sublithostatic pore fluid pressure was determined at the capture temperatures of 330–350 °C during the process of filling and/or healing of microcracks. According to constructed rheological profiles and related mechanisms, high, sublithostatic pore fluid pressure is likely to significantly weaken the fault and to be related to inception of a brittle fault slip above the brittle–ductile transition zone. A high strain rate driven by the coseismic slip in the brittle regime may lead to a brittle fault slip in the brittle–ductile transition zone, and then plastic deformation in the transition zone may resume gradually during post-seismic creep. The focal depth of the 2008 Mw 7.9 Wenchuan earthquake may be controlled by a velocity weakening to velocity strengthening transition in frictional slip (brittle regime) of granite around a temperature of 350 °C.